Functional Analysis of Centrosomal Kinase Substrates in Drosophila melanogaster Reveals a New Function of the Nuclear Envelope Component Otefin in Cell Cycle Progression. - Habermann, K.; Mirgorodskaya, E.; Gobom, J.; Lehmann, V.; Muller, H.; Blumlein, K.; Deery, M.J.; Czogiel, I.; Erdmann, C.; Ralser, M.; von Kries, J.P.; Lange, B.M. (Molecular and Cellular Biology, 2012)
Phosphorylation is one of the key mechanisms that regulate centrosome biogenesis, spindle assembly, and cell cycle progression. However, little is known about centrosome-specific phosphorylation sites and their functional relevance. Here, we identified phosphoproteins of intact Drosophila melanogaster centrosomes and found previously unknown phosphorylation sites in known and unexpected centrosomal components. We functionally characterized phosphoproteins and integrated them into regulatory signaling networks with the 3 important mitotic kinases, cdc2, polo, and aur, as well as the kinase CkII?. Using a combinatorial RNA interference (RNAi) strategy, we demonstrated novel functions for P granule, nuclear envelope (NE), and nuclear proteins in centrosome duplication, maturation, and separation. Peptide microarrays confirmed phosphorylation of identified residues by centrosome-associated kinases. For a subset of phosphoproteins, we identified previously unknown centrosome and/or spindle localization via expression of tagged fusion proteins in Drosophila SL2 cells. Among those was otefin (Ote), an NE protein that we found to localize to centrosomes. Furthermore, we provide evidence that it is phosphorylated in vitro at threonine 63 (T63) through Aurora-A kinase. We propose that phosphorylation of this site plays a dual role in controlling mitotic exit when phosphorylated while dephosphorylation promotes G(2)/M transition in Drosophila SL2 cells.